The evaluation of individuals under the age of 18 working at Şahinbey automotive industrial site in Gaziantep province - Cüce, Coşkun; Aydın, Neriman (Frontiers in Public Health, 2024)
IntroductionChild labor is an important issue of public health in both developed and developing countries. This is a cross-sectional-descriptive study.Methods418 individuals under the age of 18 were enrolled in the study. Data were collected by using a questionnaire. The data were analyzed using SPSS 22 software package. Significance was p < 0.05.ResultsAll the participants were male with a mean age of 14.90 ± 1.94 years. 34.9% did not continue education. Among them, prevalence of underweight, shortness, overweight and obesity were 3.3, 9.9, 17.7 and 6.2%, respectively. 16.5% of the families had immigrated. The mean number of family members was 5.87 ± 1.62. Out of the participants, 29.4% were smokers, 8.4% had alcohol abuse and 3.8% had substance abuse. 55.0% of the children stated to have started working for acquiring a profession, whereas 35.4% were for financial reasons. The children were working mostly at automobile repair shops (38.8%). The average working time was 11.46 ± 0.83 h per day. 5.7% of the children were attending apprenticeship school. 52.6% said they had at least one occupational injury event.DiscussionIt was found that age, reason for working, the degree of proximity to the employer, and having a master trainer’s certificate of the employer affected the children’s attendance at Apprenticeship Training Center. Occurrence of having occupational injury events was found to be associated with sleep duration, experiencing abuse, smoking and alcohol addiction. Child labor still remains unsolved despite the measures taken and the long struggle. It will be useful to support them in healthy life behaviors such as healthy sleep, healthy nutrition, no smoking and alcohol habits. More radical solutions should be sought to eliminate child labor.